SOSIALISASINILAI BUD AYA MAND AR (Studi Kasus Pada Generasi Muda di Kec. Balanipa Kabupaten Polewali Mandar, Sulawesi Barat - Idham Idham (Al-Qalam, 2007)
This research is done in Balanipa regional district of Polewali MandarWest Sulawesi. The research covers the descriptive qualitative. Thedata is found and gathered with the technique of collecting data asfollows: a) depth interview, b) document study, and c) observation. Theprocessing and data analysis are done with analyzing all preparingdata from some sources.The result of the research shows that Mandarese culture is necessary tobe socialized for the next generation because it is an identity for supportingcommunity, process of Mandarese culture socialization in somemain note of the appropriating historical development, and Madareseculture still exist to the present suitable era especially an establishmentfor the next generation, especially in the case of agreement, maintenanceof low, looking for correctness, democracy, autonomy of territory,concept of leadership, unity of the people, keep the trusteeship,solidarity, transparency, insight to the front, accountability, supervisionor care, and professionalism.